The reasons for the gap between the results of the test of secondary school students in Taif and the results of the general and achievement test - Al-Thubaiti, Khaled Safar (Journal of Educational and Psychological Sciences, 2021)
The current study aimed at the reasons for the gap between the results of the test of high school students in Taif and the results of the general aptitude and achievement test from the viewpoint of students, teachers, educational supervisors and school leaders To achieve the objectives of the study, the researcher used the descriptive and analytical approach. Two questionnaires were prepared, a questionnaire for students, and the other was distributed to teachers, supervisors and educational leaders. The study sample reached (343) by (193) students and (150) teachers, an educational supervisor and a school leader. The gap regarding students is ranked according to importance as follows: In the first place, fear of the tests leads to failure to perform with an average of (4.1), and in the second place, "students were not trained in the school on tests similar to the aptitude and achievement tests" with an average of (3.97). With regard to teachers, educational supervisors and school leaders, arranged in order of importance as follows: In the first place is "deficiency in the inclusion of samples of aptitude tests and achievement tests in the curriculum" with an average of (4.49), and in the second place is a deficiency in conducting periodic experimental tests for students during the year for training on exams Achievement abilities and tests, with an average of (4.43). In light of the results of the study, the researcher presented a set of recommendations and proposals, the most important of which are: Exercise in awe, attract trainers of the offered mental skills specialists in measurement and evaluation, design tight training bags that specialize in testing general abilities.